A marine vertebrate fauna from the Late Triassic of Somerset, and a review of British placodonts. Issue 4 (October 2015) - Nordén, Klara K.; Duffin, Christopher J.; Benton, Michael J.
Abstract: The British Rhaetian (latest Triassic) is famous for its bone beds containing abundant remains of fishes and reptiles. Most Rhaetian bone beds are assumed to have been similar in faunal composition, representing long-distance mixing of transported remains, and deposition some distance from shore. In the Mendip Hills of southwest England, some Rhaetian bone beds lie unconformably on Carboniferous Limestone, where the marine sediments of the Rhaetian Transgression lapped onto the shorelines of the palaeo-islands. The fauna from the Marston Road site, near Holwell, Shepton Mallet, in Somerset, shows a remarkable association of some coastal and terrestrial reptile remains mixed with the usual teeth and scales of sharks and bony fishes. We report unequivocal fossils of a small lepidosaur, probably a sphenodontian, a terrestrial wash-in, as well as marine reptiles, the possible thalattosaur Pachystropheus and placodonts. Sphenodontian remains are abundant in Late Triassic red bed fissure fills from nearby, and the Marston Road site provides a palaeoecological/topographic link between terrestrial and marine deposits, hinting also that the development of some of the vertebrate-bearing fissures may have been coeval with the Rhaetian transgression.